Efektivitas Penggunaan Video Animasi Sebagai Media Interaktif Untuk Siswa Sekolah Dasar di Masa Pandemi - Nurul Safira; Sistya Fhirdhan Anjani; Annisa Rizky Amalia (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Pandemic times require a teacher to guide his students to learn remotely. Effective learning should always be explored so that students' learning outcomes do not decline in pandemic times. The study aimed to find out how much percentage of students responded positively or negatively to learning using video. This research uses quantitative methods. This study obtained results from 15 elementary students who studied Natural Education (IPA). Overall results are analyzed through a percentage form based on the student's response qualifications. The study was conducted by distributing questionnaires. Through this research it was found that the use of animated learning videos is very effective because this video becomes a learning strategy in the COVID-19 pandemic. Through the analysis of the characteristics of appropriate learners, this media becomes a reference for teachers towards the implementation of learning that must use learning media that is fun and liked by students. The advantages of video as a learning medium are easy to use and able to explain content more clearly. The downside is not interactive.